Hirntoddiagnostik: Einsatz ergänzender apparativer Untersuchungen - Walter, Uwe (DMW - Deutsche Medizinische Wochenschrift, 2024)
With the determination of the definitive, irreversible loss of the overall function of the cerebrum, cerebellum and brain stem (irreversible loss of brain function, IHA, "brain death"), the death of the human being is determined from a scientific-medical point of view. The determination of IHA, with cardiovascular function being maintained by intensive care, requires special diagnostics ("brain death diagnostics"). This is carried out in the intensive care unit either to assess the medical prognosis, or as a prerequisite for post-mortem organ donation. In Germany, in accordance with the Transplantation Act, the procedural rules for determining IHA are laid down in corresponding guidelines of the German Medical Association (RL-BÄK), the 5th update of which has been in force since September 2022. Here, the indications, the requirements and the technical procedures of ancillary tests (electroencephalography, early auditory and somatosensory evoked potentials, Doppler and duplex sonography, computed tomography angiography, radionuclide perfusion scintigraphy, digital subtraction angiography) according to the German guidelines are outlined.
Keywords: irreversibler Hirnfunktionsausfall; Hirntod; apparative Zusatzverfahren